The Influence of Google Ads and Google Maps on Purchase Decisions at Bakso Royal Surabaya - Firmansyah, Andrean Putra; Augustinah, Fedianty; Sarwani, Sarwani (PT. Riset Press International, 2025)
The food and beverage industry is one of the most competitive sectors, compelling business players to leverage digital technologies like Google Ads and Google Maps to boost sales. This study aims to analyse the influence of Google Ads and Google Maps on consumer purchase decisions at Bakso Royal Surabaya. A quantitative approach was employed using surveys as the data collection technique, involving 99 respondents selected through purposive sampling. Multiple linear regression analysis results indicate that both Google Ads and Google Maps significantly influence purchase decisions, both partially and simultaneously, with a significance value of 0.000 (p < 0.05) for each. The regression coefficient values reveal that Google Maps has a greater impact than Google Ads in influencing purchase decisions. The coefficient of determination test yielded an R² value of 0.513, meaning 51.3% of the variation in purchase decisions is influenced by these two variables, while the remaining 48.7% is affected by other factors. These findings suggest that integrating digital strategies through Google Ads and Google Maps can effectively enhance business visibility and appeal, thereby positively impacting consumer purchase decisions. This study provides valuable insights for business players to optimise digital technologies to improve their competitive edge.